2006
DOI: 10.1007/s11172-006-0219-x
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium carborane complexes in the controlled radical polymerization of methyl methacrylate

Abstract: New initiators based on closo and exo nido ruthenacarboranes with phosphine and diphosphine ligands were proposed as chain growth regulators. They allow conducting the controlled synthesis of poly(methyl methacrylate) under radical initiation conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Solvents were distilled from appropriate drying agents under argon prior to use. Starting complex 1 were successfully prepared from (PPh 3 ) 3 RuCl 2 [19] and the K þ salt of the [nido-C 2 B 9 H 12 ] À monoanion by slightly modifying the earlier published procedure [5] where benzene was used as a solvent instead of Et 2 O/THF mixture [10]. Chromatography columns (ca.…”
Section: General Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Solvents were distilled from appropriate drying agents under argon prior to use. Starting complex 1 were successfully prepared from (PPh 3 ) 3 RuCl 2 [19] and the K þ salt of the [nido-C 2 B 9 H 12 ] À monoanion by slightly modifying the earlier published procedure [5] where benzene was used as a solvent instead of Et 2 O/THF mixture [10]. Chromatography columns (ca.…”
Section: General Commentsmentioning
confidence: 99%
“…In several recent reports we have demonstrated that the long-known "threebridge" exo-nido-ruthenacarborane [exo-5,6,10-{Ru(Ph 3 P) 2 Cl}-5,6,10-(m-H) 3 -10-H-nido-7,8-C 2 B 9 H 8 ] (1) [5], as well as its closo isomer [3,3-(Ph 3 P) 2 -3-Cl-3-H-closo-3,1,2-RuC 2 B 9 H 12 ] [3], can undergo facile substitution of the PPh 3 by the chelating diphosphinoalkanes [Ph 2 P(CH 2 ) n PPh 2 ] (n ¼ 2e4) [3,6] or their chiral derivatives [7,8], as well as by N,N-donor ligands such as 2,2 0 -bipyridyl derivatives [9]. As a result a series of novel diamagnetic (18-electron) and paramagnetic (17-electron) diphosphine and diamine ruthenacarborane complexes of closo and/or exo-nido types have been conveniently prepared, and some of them proved to be extremely efficient pre-catalysts for atom transfer radical polymerization (ATRP) of vinyl monomers [10]. As an extension of this work we attempted to explore the application of similar synthetic methodology to the construction of closo-ruthenacarborane complexes incorporating long-chain diphosphine ligand, 1,5-bis(diphenylphosphino)pentane (2, dppt).…”
Section: Introductionmentioning
confidence: 99%
“…The starting closo complex 3 has been synthesized ear lier by two methods: (1) according to a scheme 8 (5) in an Et 2 O-THF mixture 10 or benzene at 22 °C. 5 In the present study, we substan tially modified the latter method by using the one pot thermal reaction of complex 4 with an insignificant excess of salt 5 in benzene to prepare closo complex 3 (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…5 In the present study, we substan tially modified the latter method by using the one pot thermal reaction of complex 4 with an insignificant excess of salt 5 in benzene to prepare closo complex 3 (Scheme 2). This reaction under argon gave the target product 3 (after purification on a silica gel column and crystallization) in 51% yield.…”
Section: Resultsmentioning
confidence: 99%
“…Boron-containing transition metal clusters exhibiting ortho -cycloboronation of the phosphine or diphosphine ligands on a metal atom are long known in metallaborane [1,2,3] and monocarbon metallacarborane [4,5] chemistry. However, first examples of related 12-vertex dicarbon metallacarborane complexes were reported only recently [6,7,8,9,10,11], and all known complexes of these series are Ru III species having a 17-electron shell. In this regard it is of interest that these paramagnetic ortho -cycloboronated metallacarborane systems demonstrate the exceptionally high efficiency as catalyst precursors for the atom transfer radical polymerization (ATRP) of methyl methacrylate, as well as of other vinyl monomers [7,8,9,10,11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%